Modified mallampati classification in determining the success of unsedated transesophageal echocardiography procedure in patients with heart disease: simple but efficient. Issue 1 (December 2015) - Khongkaew, Jureerat; Sahasthas, Dujdao; Potat, Tharrittawadha; Thammawirat, Phatchara
Abstract Background The transesophageal echocardiograhpy (TEE) has been studied worldwide. However, identifying additional factors on top of operator's experience and patient's cooperation which could influence the success of the procedure in unsedated patients with heart disease is not well documented. Methods Under the cross-sectional descriptive design, 85 target patients were fulfilling the criteria: being Thai national at the age of at least 20-year-old, being performed TEE by the study participant's cardiologists, being able to communicate verbally. Seven outcomes were recorded, including gag reflex, insertion attempt, insertion time, vital signs (heart rate, oxygen saturation and mean arterial blood pressure), visible blood on TEE probe tip, and oropharyngeal pain at 1 h and 24-h. Results There were 85 eligible patients during June 2012 to June 2013. The major participants were male (46, 54 %) and the mean age was 51.2 ± 12.5 years. The MMC class III was mostly found (33, 38.80 %). TEE probe insertion time and gag reflex were indicated statistical significance (P < 0.05). Linear regression revealed that MMC class III (b 3.718; SD ± 1.077;P = 0.001) and class IV (b 5.15; SD ± 1.286;P = 0.000) were statistically associated with TEE probe insertion time, whereas MMC class II was no statistically significant (b 2.348; SD ± 1.405;P = 0.099) according to constant value in MMC class I (5.318 s). Similarly, logistic regression indicated that the patients with high grade MMC were more likely to have gagging than the low grade MMC patients (MMC 2 OR 0.567, 95 % CI 0.09–3.42, P = 0.536; MMC 3 OR 5.231, 95 % CI 1.55–17.67, P = 0.008; MMC 4 OR 3.4, 95 % CI 0.84–13.76, P = 0.086). Conclusions Modified Mallampati Classification is one of determining factors in the success of unsedated TEE procedure in patients with heart disease, especially for assessment of gagging and successful TEE probe insertion time.